Industrial training report: Petronas Resource Centre / Muhammad Safwan Rabani Hamzah - Hamzah, Muhammad Safwan Rabani (Faculty of Information Management, 2022)
Final year students are required to undergo industrial training for a period five (5) months during final semester before graduation. In addition, to complete the industrial training, it is a compulsory for students to conduct a special project, or final year project at their respective industrial training workplace. The semester seven (7) students enrolling in Bachelor of Information Science (Hons.) Library Management will be regarded completed after submission of the report and presentation. The student had chosen to conduct his industrial training at PETRONAS Resource Centre, Kuala Lumpur. The content of this report contains the five (5) months industrial training progress, activities, and involvement at PETRONAS Resource Centre. This report consists of five (5) chapters in sequence, starting with the introduction, organization information, industrial training activities, industrial training reflection, and conclusion. This report also comprehended with appendices and logbook that records the daily activities of the student during his industrial training.